Peran Bank Wakaf Mikro Lirboyo dalam Meningkatkan Inklusi Keuangan Syariah Pelaku Umkm Kediri Perspektif Kesejahteraan Islam - Ilyas Adhi Purba; Ali Samsuri; Muhamad Wildan Fawa'id (Journal of Islamic Economics (JoIE), 2022)
One of the government's strategies in increasing Islamic financial inclusion is an empowerment program for micro business actors through the Micro Waqf Bank (BWM). In the city of Kediri there is a BWM which has quite good development in helping the community's economic growth, one of which is BWM Berkah Rizqi Lirboyo. Utilization of access to sharia finance provided by BWM Berkah Rizqi Lirboyo, will certainly have a positive impact on the customer's economy. The various benefits that customers get will lead to the realization of community welfare. As Muslims, the achievement of prosperity also needs to be considered from an Islamic perspective. Therefore, this study wants to examine the role of BWM Berkah Rizqi Lirboyo in increasing Islamic financial inclusion in the perspective of Islamic welfare. This research is included in the type of field research. The data collection technique used observation, documentation, and interviews with the relevant informants. The results of this study indicate that the role of BWM Berkah Rizqi Lirboyo in increasing Islamic financial inclusion through access to qardhul hasan financing, financing supervision through KUMPI and HALMI, and realizing the dimensions of financial inclusion well. Based on the perspective of Islamic welfare according to Al-Ghazali, five basic things must be fulfilled in maqashid sharia. These five basic needs have been fulfilled by customers, so that the welfare of customers from an Islamic perspective has been fulfilled.Salah satu strategi dari pemerintah dalam meningkatkan inklusi keuangan syariah adalah program pemberdayaan pada pelaku usaha mikro melalui Bank Wakaf Mikro (BWM). Di Kota Kediri terdapat BWM yang memiliki perkembangan cukup baik dalam membantu pertumbuhan perekonomian masyarakat, salah satunya adalah BWM Berkah Rizqi Lirboyo. Pemanfaatan akses keuangan syariah yang diberikan BWM Berkah Rizqi Lirboyo, tentu akan memberikan dampak positif pada perekonomian nasabah. Berbagai manfaat yang didapatkan nasabah akan mengarah pada terwujudnya kesejahteraan masyarakat. Sebagai umat muslim, tercapainya suatu kesejahteraan juga perlu memperhatikan dalam perspektif Islam. Oleh karena itu, penelitian ini ingin meneliti peran BWM Berkah Rizqi Lirboyo dalam meningkatkan inklusi keuangan syariah dalam perspektif kesejahteraan Islam. Penelitian ini termasuk dalam jenis penelitian lapangan. Teknik pengambilan data menggunakan teknik observasi, dokumentasi, serta wawancara kepada narasumber yang bersangkutan. Hasil penelitian ini menunjukan bahwa peran BWM Berkah Rizqi Lirboyo dalam meningkatkan inklusi keuangan syariah melalui akses pembiayaan qardhul hasan, pengawasan pembiayaan melalui KUMPI dan HALMI, dan mewujudkan dimensi inklusi keuangan dengan baik. Berdasarkan perspektif kesejahteraan Islam menurut Al-Ghazali, maka harus terpenuhi lima hal dasar pada maqashid syariah. Para nasabah telah terpenuhi lima kebutuhan dasar tersebut, sehingga kesejahteraan nasabah perspektif Islam telah terpenuhi.